A Collision Tumor: Reflectance Confocal Microscopy Features and Correlation between Dermoscopy and Histopathology - Savas, Sevil; Yuksel, Esma Inan; Erdemir, Ash Vefa; Gurel, Mehmet Salih; Leblebici, Cem (Wolters Kluwer Medknow Publications, 2019)
Coexistence of two types of malignant neoplasms, called 'a collision tumor', is relatively uncommon. Basal cell carcinomas (BCCs) are known to coexist with other cutaneous lesions, but the collision of BCC with malignant melanoma is rare. We report a rare case of BCC with underlying lentigo maligna melanoma, focusing on dermoscopic and reflectance confocal microscopic (RCM) findings and their correlation with histopathology. RCM and dermoscopy seem to offer important clues to increase clinical suspicion of collision tumors and improve clinical diagnosis.
Keywords: Basal cell carcinoma; collision tumor; melanoma; reflectance confocal microscopy